Qualidade de sementes de soja resfriadas sob sistema dinâmico, armazenadas em ambiente climatizado e temperatura ambiente - Dellagostin, Simone Morgan (2016)
The seed technology is associated to the development of efficient procedures for production, trading and use of lots with high quality seeds. In Brazil, the dynamic cooling of soybean seeds is carried out before bagging and consists on injecting cold air into the seed mass in order to reduce temperature and seed deterioration during storage. In this context, this trial aimed at analyzing soybean seeds that were cooled under dynamic system and stored in air-conditioned warehouse, seeds that were not cooled but stored in air-conditioned warehouse, and seeds that were not cooled but they were stored at room temperature in a conventional warehouse. The following control tests of quality were analyzed: water content, one hundred-seed mass, germination, seedling growth and emergence in sand at the beginning and every thirty days, throughout the whole storage period. Tests of purity, tetrazolium, accelerated aging, sodium hypochlorite, controlled deterioration and cold test were also carried out at the beginning of the experiment. The applied methodologies were determined by RAS (Rules for Seed Analysis) and set by the Ministry of Agriculture, Livestock and Supply. The trial was carried out based on a completely randomized design. The data were submitted to analysis of variance and linear regression. There was no statistical difference among the studied treatments. Seeds kept their physical and physiological quality throughout the storage period. Dynamic cooling is not justified for seeds with high physiological performance.